Gender differences in music search behaviour on social Q&A sites: A case study on Zhihu. Issue 1 (1st February 2019) - Deng, Shengli; zhao, Anqi; Huang, Ruhua
ABSTRACT: In spite of ample studies on music information behaviour, little is known on how music search behaviour is performed on social question and answer (social Q&A) sites by considering gender differences. Based on a collection of 12, 331 music questions collected from Zhihu, the study adopted a mixed research methodology and performed both quantitative analysis and qualitative content analysis to explore gender differences in music search behaviour on social Q&A sites. The results show that males are associated with more questions, answers and followers than females. Males asked question on social Q&A sites mainly for seeking ready reference, whereas females often asked question to promote a discussion. When formulating questions, females tend to use second pronouns and interrogative words like "what" more often than males. In contrast, questions from males tend to include more words and are thus longer than the questions from females. In addition, questions asked by males tend to attract more answers than those from females. Our results shed light to current music information behaviour studies and contribute new insights to the development of a better music service system.